Magnoflorine Alleviates “M1” Polarized Macrophage-Induced Intervertebral Disc Degeneration Through Repressing the HMGB1/Myd88/NF-κB Pathway and NLRP3 Inflammasome - Zhao, Feng; Guo, Zhenye; Hou, Fushan; Fan, Wei; Wu, Binqiang; Qian, Zhonglai (Frontiers in Pharmacology, 2021)
Intervertebral disc degeneration (IDD) is related to the deterioration of nucleus pulposus (NP) cells due to hypertrophic differentiation and calcification. The imbalance of pro-inflammatory (M1 type) and anti-inflammatory (M2 type) macrophages contributes to maintaining tissue integrity. Here, we aimed to probe the effect of Magnoflorine (MAG) on NP cell apoptosis mediated by “M1” polarized macrophages. THP-1 cells were treated with lipopolysaccharide (LPS) to induce “M1” polarized macrophages. Under the treatment with increasing concentrations of MAG, the expression of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α, IL-18), high mobility group box protein 1 (HMGB1), as well as myeloid differentiation factor 88 (MyD88), nuclear factor kappa B (NF-κB) and NOD-like receptor 3 (NLRP3) inflammasomes in THP-1 cells were determined. What’s more, human NP cells were treated with the conditioned medium (CM) from THP-1 cells. The NP cell viability and apoptosis were evaluated. Western blot (WB) was adopted to monitor the expression of apoptosis-related proteins (Bax, Caspase3, and Caspase9), catabolic enzymes (MMP-3, MMP-13, ADAMTS-4, and ADAMTS-5), and extracellular matrix (ECM) compositions (collagen II and aggrecan) in NP cells. As a result, LPS evidently promoted the expression of pro-inflammatory cytokines and HMGB1, the MyD88-NF-κB activation, and the NLRP3 inflammasome profile in THP-1 cells, while MAG obviously inhibited the "M1" polarization of THP-1 cells. After treatment with “M1” polarized THP-1 cell CM, NP cell viability was decreased, while cell apoptosis, the pro-inflammatory cytokines, apoptosis-related proteins, and catabolic enzymes were distinctly up-regulated, and ECM compositions were reduced. After treatment with MAG, NP cell damages were dramatically eased. Furthermore, MAG dampened the HMGB1 expression and inactivated the MyD88/NF-κB pathway and NLRP3 inflammasome in NP cells. In conclusion, this study confirmed that MAG alleviates “M1” polarized macrophage-mediated NP cell damage by inactivating the HMGB1-MyD88-NF-κB pathway and NLRP3 inflammasome, which provides a new reference for IDD treatment.